Socio-territorial GIS as a tool to support Coastal Management - Pinho, L. (2013)
Nowadays, geographic information systems are an indispensable tool in land use management. Namely in coastal areas where population is and economic activities are concentrated, and where territorial conflict is common between the environmental, social and economical systems, this tool can be of great importance. On teh other hand the climate change aggravation - increase of the frequency and intensity of extreme events - causing changes in coastal dynamics and intensifying coastal conflicts justify the use of this tool even more. In this context, the design of a geographic information system with particular attention to coastal dynamics, coastal erosion and coastal risks, and integrating territorial and socio-economical data, can be decisive. The crossing og all this information, namely technical data, scientific data and social perception results, only in one tool should allow a more efficient coastal management policymaking thus allowing, in an a priori phase, the surveying of the populations' availability to accept the measures that governments or institutions intend to implement.